Physiotherapists' Experiences with “Sterk og Stødig” for Home-Dwelling Older Adults – A Qualitative Study - Ane Brekke; Bård Erik Bogen; Ingebjørg Kyrdalen; Lill Anette Juvik (Fysioterapeuten)
Aim: To explore physiotherapists' experiences with recruiting, training, and supervising volunteer instructors responsible for leading Sterk og stødig (English: Strong and Steady) exercise groups as part of the municipality's fall prevention services for home-dwelling older adults.